Regulatory T Cell Activity and Signs of T Cell Unresponsiveness in Bovine Paratuberculosis - Roussey, Jonathan A.; Steibel, Juan P.; Coussens, Paul M. (Frontiers in Veterinary Science, 2014)
Johne’s disease, caused by infection with Mycobacterium avium subspecies paratuberculosis (MAP), is a wasting disease of ruminants displaying a long subclinical stage of infection followed by clinical disease characterized by severe diarrhea, wasting, and premature death. Immunologically, subclinical disease is characterized by a Th1 response effective at controlling intracellular infections such as that caused by MAP. In late subclinical disease, the Th1 response subsides and a non-protective Th2 response becomes prominent. One hypothesis for this shift in immune paradigm is that a population of MAP-reactive regulatory T cells (Tregs) develops during subclinical infection, limiting Th1-type responses to MAP antigens. To investigate this we sought to accomplish the following: 1) Determine if CD4+CD25- T cells exposed to MAP-infected macrophages develop a Treg phenotype, 2) Develop a method to expand the relative abundance of Tregs in bovine peripheral blood lymphocyte populations, and 3) Identify functional activities of expanded Tregs when combined with autologous peripheral blood mononuclear cells (PBMCs) and live MAP. We found that CD4+CD25- T cells exposed to MAP-infected macrophages from cows with Johne’s disease do not show signs of a Treg phenotype and appear unresponsive to MAP antigens. A method for Treg expansion was successfully developed; however, based on results obtained in the subsequent functional studies it appears that these Tregs are not MAP-specific. Overall, it seems that T cell unresponsiveness, rather than Treg activity, is driving the Th1-to-Th2 immune shift observed during Johne’s disease. Further, we have successfully developed a method to enrich non-specific bovine Tregs that exert suppressive effects against Th1 cytokine production.